2019
DOI: 10.1002/jcb.28633
|View full text |Cite
|
Sign up to set email alerts
|

Association between the flap endonuclease 1 gene polymorphisms and cancer susceptibility: An updated meta‐analysis

Abstract: Flap endonuclease 1 (FEN1) has emerged as an important enzyme in the maintenance of genomic instability and preventing carcinogenesis. The relationship between FEN1 −69G>A (rs174538)+4150G>T (rs4246215) polymorphisms and cancer susceptibility has been reported; however, results were inconclusive. In the present study, a meta-analysis of data from eligible reports was carried out to summarize the possible relationship between FEN1 polymorphisms and cancer risk. A total of 11 articles, including 20 studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As a structure-specific endonuclease, Flap endonuclease 1 (FEN1) plays vital roles in DSB repair via HR and MMEJ, as well as through the long patch base excision repair (LP-BER) pathway 19 , 27 , 28 . A higher level of FEN1 expression was detected in rapidly dividing cells, including various types of cancer cells, than in cells with normal division kinetics and is associated with enhanced malignancy and decreased survival rates 29 31 . In addition, robust evidence revealed that silencing FEN1 leads to enhanced cisplatin sensitivity in glioma 32 , indicating a potential strategy for glioma cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As a structure-specific endonuclease, Flap endonuclease 1 (FEN1) plays vital roles in DSB repair via HR and MMEJ, as well as through the long patch base excision repair (LP-BER) pathway 19 , 27 , 28 . A higher level of FEN1 expression was detected in rapidly dividing cells, including various types of cancer cells, than in cells with normal division kinetics and is associated with enhanced malignancy and decreased survival rates 29 31 . In addition, robust evidence revealed that silencing FEN1 leads to enhanced cisplatin sensitivity in glioma 32 , indicating a potential strategy for glioma cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The association between this SNP and the potential risk of different types of cancers, including esophageal, lung, gastrointestinal, gallbladder, breast cancer in Chinese and Iran populations, glioma and childhood leukemia, has been previously studied. The rs4246215 variant was also associated with colorectal cancer in East Asians and the Chinese population (Chou et al 2017;Moazeni-Roodi et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…The association between this SNP and the potential risk of different types of cancers, including esophageal, lung, gastrointestinal, gallbladder, breast cancer in Chinese and Iran populations, glioma and childhood leukemia, has been previously studied. The rs4246215 variant was also associated with colorectal cancer in East Asians and the Chinese population ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%